Дуальная система Аппеля и пространства Кондратьева в анализе на пространствах Шварца - Качановский, Н.А. (Український математичний журнал, 1997)
Вивчаються біортогоиальна система Аппеля та простори Кондратьева при умові збурення параметра μ-експонеиціалу голоморфннми оборотними функціями. Одержані результати застосовуються для вивчення псевдодиференціальних рівнянь. We study the biorthogonal Appell system and Kondrat’ev spaces in the case where the parameter of a μ-exponential is perturbed by holomorphic invertible functions. The results obtained are applied to the investigation of pseudodifferential equations.